Optic bionanospherical probe from Gd\(_2\)O\(_3\): Yb, Er upconverting nanosphere and mAb^CD133 antibody for precise imaging label of cancer stem cell NTERA-2 - Nguyen, Huong; Do, Thi Thao; Nguyen Trong, Nghia; Nguyen Thi, Nga; Pham Thi, Lien; Ha Thi, Phuong; Nguyen Van, Nghia; Vu, Duong; Tran Thu, Huong; Tran Kim, Anh; Le, Quoc Minh (Communications in Physics, 2023)
Rare earth photonic nanomaterials are increasingly prominently applied in various fields of biomedicine. Currently, there is greater focus on the investigation to control the size and shape of nanomaterials, including the nanospherical form, which allows for precise labeling by only one nanoparticle. This paper demonstrates, for the first time, the construction of a biological nanospherical probe (BNSP) Gd2O3: Yb3+, Er3+/Silica/NH/mAb^CD133 for diagnostic labeling of cancer stem cells (CSCs) NTERA-2. The BNSP was constructed using highly monodisperse spheres with around 200nm uniform size of Gd2O3: 7.6% Yb3+, 1.6% Er3+. They were functionalized by an amine group-contained shell coating and conjugated with CD133 monoclonal antibody. The functionalized nanosphere Gd2O3: Yb, Er/silica/NH2 showed strong upconversion luminescence in red color upon laser excitation in the near-infrared region at 975 nm. The Gd2O3: Yb3+, Er3+/silica/NH2 was carefully implemented to conjugate mAb^CD133 via a linker, glutaraldehyde, to obtain the predictable probe Gd2O3: Yb3+, Er3+/Silica/NH/mAb^CD133. Then, this BNSP was tested in vitro for its capacity to label NTERA-2 cancer stem cells. The efficient labeling based on the fluorescent immunoassay method was detected by incorporating a nanophotometer, Field Energy Scan Electron Microscopy (FESEM), and precisely determined by fluorescent microscopy. The study shows that the BNSP is highly efficient with targeting capacity and specificity in the labeling of cancer stem cells. These advanced results open up promising avenues for the development of precise imaging diagnostics in cancer cellular biomedicine, and beyond.